The Effect of Destination Image and Perceived Value on Tourist Satisfaction and Tourist Loyalty of Bedugul Botanical Garden, Bali - Tedjakusuma, Adi Prasetyo; Retha, Ni Komang Meyintha Dewi; Andajani, Erna (Universitas Muhammadiyah Jakarta, 2023)
This study aims to examine the effect of destination image and perceived value on tourist satisfaction and tourist loyalty of Bedugul Botanical Garden visitors. The object of this study is Bedugul Botanical Garden in Bali Indonesia. This study is basic research and based on its objectives, this research is causal with the aim of knowing the relationship between two or more variables (variables in this study are destination image, perceived value, tourist satisfaction and tourist loyalty) in order to find an explanation of a research question. The data source used in this research is primary data obtained directly from 140 respondents through distributing questionnaires online and offline. The sampling technique of this study was non-probability sampling. Data were analyzed using Structural Equation Model (SEM) technique using AMOS software. The results show that Destination Image has a positive and significant influence on Perceived Value; Perceived Value has a positive and significant influence on Tourist Satisfaction and Tourist Loyalty; and Tourist Satisfaction has a positive and significant influence on Perceived Value if the Bedugul Botanical Garden. While, Destination Image has a negative and insignificant influence on Tourist Satisfaction and Tourist Loyalty of the Bedugul Botanical Garden.